KESIAPAN GURU BAHASA INDONESIA DALAM MENERAPKAN PEMBELAJARAN MENDALAM - Azzahra, Sabina Nur; Wahyuni, Primasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the readiness of Indonesian language teachers in implementing deep learning and to identify the obstacles they face and the solutions they apply. A descriptive method combining quantitative and qualitative approaches through data triangulation was used, involving 12 Indonesian language teachers at SMK Negeri 1 Kasihan, SMK Negeri 2 Yogyakarta, and SMA Negeri 1 Sedayu, selected through purposive sampling. Data were collected through a Likert-scale questionnaire, semi-structured interviews, and documentation, then analyzed using descriptive statistics and the Miles and Huberman qualitative data analysis model. The results show that teacher readiness generally falls into the “Very Ready” category, with an overall mean questionnaire score of 3.33 out of a maximum of 4.00. Teachers faced obstacles such as limited technological proficiency, limited school facilities, administrative workload, heterogeneity of student ability, and a lack of practical socialization, which were addressed through training and workshops, empowering subject-teacher forums (MGMP) and learning communities, independent learning, differentiated instruction, and regular reflection. This study recommends strengthening continuous professional development and the equitable distribution of technological facilities to support the optimal implementation of deep learning.